Perilaku Menabung Mahasiswa Berdasarkan Literasi Keuangan, Teman Sebaya, dan Uang Saku - Kunardi, Elisabet Yohana; Setyawan, Surya (Jurnal Manajemen Bisnis dan Keuangan, 2025)
The increasing use of the internet in Indonesia is driven by the convenience that technology offers in various aspects of human life. A notable phenomenon among society, particularly university students, reveals a strong tendency toward consumptive behavior in today’s digital era. When facing financial difficulties, saving becomes an essential strategy for achieving financial goals. This study aims to analyze the influence of financial literacy, peer influence, and allowance on the saving behavior of students in the Management and Accounting programs at Maranatha Christian University. The research employed a quantitative approach with a purposive sampling technique, involving 91 students as respondents. Data were analyzed using multiple linear regression with SPSS software. The findings indicate that peer influence, allowance, and financial literacy collectively affect students’ saving behavior. There is a correlation of 82.1% between saving behavior (Y) and the three factors: financial literacy (X₁), peer influence (X₂), and allowance (X₃). These results highlight that to develop healthy saving habits, students need to possess strong financial understanding, be surrounded by a supportive peer environment, and manage their allowance wisely.